1986
DOI: 10.1002/pd.1970060312
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of prenatal diagnosis of hereditary triose phosphate isomerase deficiency

Abstract: Prenatal diagnosis has been performed on umbilical cord blood of an 18 weeks fetus of heterozygous triosephosphate isomerase (TPI) deficient parents. After excluding maternal blood contamination, TPI activity was measured and found to be 60 per cent of the normal mean whereas the value of glucose-6-phosphate dehydrogenase activity was in the normal range of fetal blood. In addition, the analysis of the characteristics of fetal TPI, i.e. Km measurements for glyceraldehyde-3-phosphate, heat stability tests and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Two pregnancies at risk were monitored by enzyme assay of cultured amniotic cells, which disclosed a heterozygous and unaffected fetus (Clark et al, 1985). Another prenatal diagnosis has been performed at 18 weeks on umbilical cord blood sampled from a fetus at risk which was found to be a heterozygote (Rosa et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two pregnancies at risk were monitored by enzyme assay of cultured amniotic cells, which disclosed a heterozygous and unaffected fetus (Clark et al, 1985). Another prenatal diagnosis has been performed at 18 weeks on umbilical cord blood sampled from a fetus at risk which was found to be a heterozygote (Rosa et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…About 30 patients with this defect have been reported (Dreyfus and Khan, 1984;Valentine and Paglia, 1984;Rosa et al, 1985). In some the mutation resulted in a decreased activity in the range of 3-10 per cent of controls, while in others reduced heat stability or modified electrophorectic patterns have been found (Skala et al, 1977;Vives-Corrons et al, 1978;Kaplan et al, 1968;Asakawa et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal diagnosis of TPI deficiency is justified by the often severe and fatal course of disease. Several authors have described biochemical enzyme analysis in fetal cord blood samples (Bellingham et al 1989, Clark & Szobolotzky 1985, Rosa et al 1986). However, there are only limited data on the normal values of enzyme activity and substrate concentrations with respect to gestational age (Lestas et al 1982, Nicolaides et al 1985.…”
mentioning
confidence: 99%
“…These physical characteristics are generally accompanied by a decrease in enzyme activity in all tissues and an increase in the levels of DHAP in erythrocytes (Orosz et al, 2006). Although prenatal detection has become available, there has been no effective therapy developed for TPI deficiency and treatment is generally only supportive (Pekrun et al, 1995;Poinsot et al, 1986;Rosa et al, 1986). A number of studies have reported some limited success with enzyme replacement therapy (Ationu and Humphries, 1998;Ationu et al, 1997;Ationu et al, 1999a;Ationu et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%